2012
DOI: 10.1186/1476-4598-11-37
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle conferred microRNA profiles - implications in the transfer and dominance of cancer traits

Abstract: BackgroundMicroparticles (MPs) are membrane vesicles which are released from normal and malignant cells following a process of budding and detachment from donor cells. MPs contain surface antigens, proteins and genetic material and serve as vectors of intercellular communication. MPs comprise the major source of systemic RNA including microRNA (miRNA), the aberrant expression of which appears to be associated with stage, progression and spread of many cancers. Our previous study showed that MPs carry both tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 64 publications
4
99
0
Order By: Relevance
“…In contrast, the exosomal microRNA content was found to be similar to that in the original tumor, thus giving the idea of their possible use as diagnostic marker [12]. However, an abundance of certain micro RNAs that are absent or present at very low levels in the parental cells has recently been noticed [101,102]. These shows that some microRNAs may be preferentially released.…”
Section: Techniques For Isolation and Identification Of Exosomesmentioning
confidence: 71%
“…In contrast, the exosomal microRNA content was found to be similar to that in the original tumor, thus giving the idea of their possible use as diagnostic marker [12]. However, an abundance of certain micro RNAs that are absent or present at very low levels in the parental cells has recently been noticed [101,102]. These shows that some microRNAs may be preferentially released.…”
Section: Techniques For Isolation and Identification Of Exosomesmentioning
confidence: 71%
“…For example, miR-638 may be stably detected in human plasma, and the miR-92/miR-638 ratio in plasma may be a useful indicator to distinguish between patients with leukemia and the healthy control group (27). Jaiswal et al (28) identified that miR-1246, miR-1308, miR-638 and other human miRNAs may be selectively enriched in microparticles, transferring them to the recipient cells. Similarly, the results of the present study identified that MVs, which cannot be distinguished from microparticles at present, package miR-638.…”
Section: Discussionmentioning
confidence: 99%
“…147 miR-455-3p has been related to P-gp levels in human ALL cell lines by mechanisms not fully understood, as will be referred in "P-gp and the microRNAs Involved in its Regulation May Be Present in Microvesicles and Exosomes, and May Be Transferred Between Cells" below. 148 …”
Section: Mirs Acting At the Transcriptional Levelmentioning
confidence: 99%
“…160 Other recent work also demonstrated that some miRs that are shed from microvesicles play an important role in MDR. 148 The authors observed that one of the significantly expressed and shed miRs, miR-455-3p, is possibly related to P-gp levels. In this study, results from microarray analysis showed that miR-455-3p was less expressed in a P-gp overexpressing resistant leukemia cell line, when compared with the parental sensitive cell line.…”
Section: P-gp and The Micrornas Involved In Its Regulation May Be Prementioning
confidence: 99%
See 1 more Smart Citation